2007
DOI: 10.1186/1471-2164-8-460
|View full text |Cite
|
Sign up to set email alerts
|

Denoising inferred functional association networks obtained by gene fusion analysis

Abstract: BackgroundGene fusion detection – also known as the 'Rosetta Stone' method – involves the identification of fused composite genes in a set of reference genomes, which indicates potential interactions between its un-fused counterpart genes in query genomes. The precision of this method typically improves with an ever-increasing number of reference genomes.ResultsIn order to explore the usefulness and scope of this approach for protein interaction prediction and generate a high-quality, non-redundant set of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Overall, we observed that the more proteomes we used for the comparison with T. brucei , the more fusion events were identified (Figure 2A). Additionally, the number of events found in each organism shows a positive correlation, in general, with the size of the proteome examined (Figure 2B), as has been described previously [9], [11], [12].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Overall, we observed that the more proteomes we used for the comparison with T. brucei , the more fusion events were identified (Figure 2A). Additionally, the number of events found in each organism shows a positive correlation, in general, with the size of the proteome examined (Figure 2B), as has been described previously [9], [11], [12].…”
Section: Resultssupporting
confidence: 83%
“…Several studies using this technique have been published, but most have focused on bacteria and fungi [9], [12], [26], [27], [28]. A preliminary analysis for T. brucei included only a small number of organisms [5], whereas in this study, we chose organisms so that they would represent every major lineage of the tree of life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, the idea is that proteins that are encoded by different genes in one organism but fused together in another are very likely to physically interact, or at least be functionally related, when expressed as separate gene products. This has been supported by comprehensive analyses (Enright and Ouzounis, 2001; Yanai et al., 2001; Marcotte and Marcotte, 2002; Kamburov et al., 2007; Reid et al., 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these co-occurring domains are fused together to form a single domain/protein in some reference organisms (Kamburov et al , 2007). In addition to deducing one-to-one DDI patterns, K-GIDDI was also designed to detect these one-to-many or many-to-many DDI patterns, which may be biologically meaningful interaction templates.…”
Section: Methodsmentioning
confidence: 99%